2021
DOI: 10.1021/acs.chemmater.1c00590
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculations Meet Experiment to Explain the Luminescence Properties and the Presence of Defects in m-ZrO2

Abstract: The present article is a thorough quantum mechanics investigation based on DFT method targeting the opto-electronic properties of the m-ZrO 2 material issuing from the presence of defects. Herein, we conclude that the luminescence observed around 477 nm (∼2.60 eV) corresponds to the charge transfer between Ti Zr and oxygen atoms (i.e., Ti 3+ + O -→ Ti 4+ + O 2 -), and not from oxygen vacancies or d -d transitions at Ti 3+ sites. Namely, based on constrained DFT calculations, an emission at 2.61 eV (475 nm) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…Typically, the synthesized ZrO 2 sample exhibits 5–10% of the tetragonal phase along with the monoclinic phase. According to the literature, a prominent PL peak appears in the range 390–425 nm for a pure tetragonal structure , with a lifetime decay smaller than 10 ns. ,, A PL peak is reported between 475 and 500 nm for monoclinic ZrO 2 , with a corresponding lifetime decay of up to a few μs (<20 μs). , As far as monoclinic ZrO 2 is concerned, the origin of the prominent emission band (expected in the range 475–500 nm) is still a matter of debate. Several reports attribute this band to the inherent presence of impurity titanium ions (Ti 3+ ) ,,, and this hypothesis is supported by density functional theory (DFT) calculations . However, the presence of Ti 3+ ions in monoclinic ZrO 2 is not seen in EPR measurements or no experimental evidence is provided for the presence of Ti 3+ ions. ,, Another model suggested that the PL emission peak at 475–500 nm is related to oxygen vacancies, ,,, as observed through EPR analysis, confirming the presence of F + centers, which are ascribed to singly charged oxygen vacancies .…”
Section: Introductionmentioning
confidence: 92%
“…Typically, the synthesized ZrO 2 sample exhibits 5–10% of the tetragonal phase along with the monoclinic phase. According to the literature, a prominent PL peak appears in the range 390–425 nm for a pure tetragonal structure , with a lifetime decay smaller than 10 ns. ,, A PL peak is reported between 475 and 500 nm for monoclinic ZrO 2 , with a corresponding lifetime decay of up to a few μs (<20 μs). , As far as monoclinic ZrO 2 is concerned, the origin of the prominent emission band (expected in the range 475–500 nm) is still a matter of debate. Several reports attribute this band to the inherent presence of impurity titanium ions (Ti 3+ ) ,,, and this hypothesis is supported by density functional theory (DFT) calculations . However, the presence of Ti 3+ ions in monoclinic ZrO 2 is not seen in EPR measurements or no experimental evidence is provided for the presence of Ti 3+ ions. ,, Another model suggested that the PL emission peak at 475–500 nm is related to oxygen vacancies, ,,, as observed through EPR analysis, confirming the presence of F + centers, which are ascribed to singly charged oxygen vacancies .…”
Section: Introductionmentioning
confidence: 92%
“…It is already known that the green emission of ZrO 2 :Ti originates from the charge transfer of Ti. 50 After fluorination, the d−d transition of Ti 3+ may lead to the yellow emission. Surprisingly, the excitation and emission spectra of ZrO 0.46 F 3.08 :Ti and ZrO 0.33 F 3.33 :Ti are sufficiently similar, the emission peaks of both are located in the UV range, appearing at 343 and 340 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Both ZrO 2 :Ti and Zr 7 O 9 F 10 :Ti emit in the visible light range, with a green emission at 470 nm and a yellow emission at 512 nm, respectively. It is already known that the green emission of ZrO 2 :Ti originates from the charge transfer of Ti . After fluorination, the d–d transition of Ti 3+ may lead to the yellow emission.…”
Section: Resultsmentioning
confidence: 99%
“…3d levels of Ti lie between VBM and CBM, close to conduction band (CB) levels of Zr. These orbitals are sufficiently far from the CBM that electrons in the CB are easily captured by Ti states, as already demonstrated by some of us for the ZrO 2 material …”
Section: Methodsmentioning
confidence: 99%